Pengaruh Pemahaman Akuntansi, Literasi Perpajakan dan Literasi Wirausaha terhadap Minat Menjadi Konsultan Pajak dengan Literasi Teknologi sebagai Pemoderasi - Tambun, Sihar; Nurjamilah, Siti; Sitorus, Riris Rotua (Universitas 17 Agustus 1945 Jakarta, 2025)
This study aims to analyze the influence of accounting understanding, tax literacy, and entrepreneurial literacy on the interest in becoming a tax consultant, with technological literacy as a moderating variable. The research employs a quantitative approach using a survey method with 178 accounting students from several universities in Indonesia as respondents. Data were analyzed using Structural Equation Modeling–Partial Least Square (SEM-PLS) with SmartPLS 3.0 software. The results show that accounting understanding and tax literacy have a positive and significant effect on the interest in becoming a tax consultant. In contrast, entrepreneurial literacy, technological literacy, and the moderating effect of technological literacy are not significant. The coefficient of determination (R²) value of 0.462 indicates that the independent variables explain 46.2% of the variation in the interest in becoming a tax consultant. These findings confirm that mastery of accounting concepts and understanding of the tax system remain the primary factors influencing students’ interest in pursuing a career as a tax consultant. Meanwhile, entrepreneurial and technological literacy have not yet become dominant factors in career decision-making in the taxation field. This research provides insights for educational institutions to strengthen practice-based accounting and digital taxation curricula to enhance students’ readiness to face the transformation of the taxation profession in the digital era